CYBER-NOTARIES FROM A CONTEMPORARY LEGAL PERSPECTIVE: A PARADOX IN INDONESIAN LAWS AND THE MARGINAL COMPROMISES TO FIND EQUILIBRIUM - Tan, David (Indonesia Law Review, 2020)
Notaries in Indonesia have existed since the colonial period. Changes in technology and the continuous evolution of information bring a flow of change in all aspects of life, including the legal sector. However, the position of notaries in Indonesia has not undergone significant changes despite ongoing advancements. The promulgation of Law No. 2 of 2014 formally introduced the term “cyber notary” to Indonesian law. However, the idea of cyber notary is not practical because of legal obstacles that seem to form a legal paradox. This work analyzes the position of cyber notaries in Indonesia’s positive legal order and the challenges, adaptations, and compromises actually made to implement cyber notaries in Indonesia. Normative–juridical legal research is adopted as a research method by examining various legal theories and performing comparisons of related laws. This work also presents examples of successful cyber notary implementations from several countries. Results reveal that the implementation of cyber notaries in Indonesia has yet to meet expectations because interrelated laws still create legal paradoxes. This condition results in the inability of notaries in Indonesia to fully evolve into cyber notaries. Recommendations for stakeholders are presented as valuable insights.